PENERAPAN PIDANA TERHADAP KETIDAKPATUHAN NOTARIS ATAS DASAR TIDAK MELAPOR SURAT PEMBERITAHUAN TAHUNAN (SPT) PAJAK PENGHASILAN (PPh) - Arinda Praminingrat, I Gusti Agung Istri; Yusa, I Gede (Acta Comitas, 2025)
This article seeks to explain the regulations concerning criminal sanctions for Notaries who fail to meet their obligation to report SPT PPh in accordance with Indonesian laws and regulations. Additionally, it aims to analyze the normative factors that contribute to the non-compliance of Notary officials in submitting SPT PPh reports. This research adopts a normative legal approach by analyzing legal materials, including laws and regulations, legal doctrines, and court rulings.The results of the study of Article 39 letter C of the KUP Law, which states that taxpayers who intentionally do not report or submit SPT PPh with incorrect information can be subject to criminal sanctions in the form of imprisonment between 6 months to 6 years and a fine of between two and four times the amount of tax that is lacking or unpaid. The basis that influences the impropriety of notary officials in reporting SPT PPh is due to the following: lack of understanding of tax law, professional attitudes and ethics, economic pressures and business practices, lack of supervision and law enforcement, social and cultural elements, and limited resources.